TECHNICAL SKILLS DIFFERENCES BETWEEN WINNING AND LOSING MATCH IN SEPAKTAKRAW THAILAND LEAGUE - Kacha Udomtaku,; Kurusart Konharn, (Sport Scientific And Practical Aspects, 2025)
The analysis of technical skills in sepaktakraw player during competition is important guidelines for planning training program. The aim of this study was to compare the differences of technical skills between winner and loser team in Sepaktakraw Thailand League. The video was record in 28 sets (14 matches) in Sepaktakraw Thailand League players by two hi-speed cameras video behind the court and perfect view of the side court. The 13 technical skills (service in, service ace, service out, services net, serve all, success first ball, unsuccessful first ball, successful feeding, unsuccessful feeding, success strike, unsuccessful strikes, successful blocking, and unsuccessful blocking) had evaluated. Independent sample t-test was performed to compare between winning and losing team. Results showed the winning team was significant differences with losing team for serve net, success strike and success blocking (p<0.05). These findings provide valuable data for trainers and athletes for training in some specific essential skills as important factors for winning in a match